2009
DOI: 10.1111/j.1654-1103.2009.01067.x
|View full text |Cite
|
Sign up to set email alerts
|

Positive effects of shrubs on herbaceous species richness across several spatial scales: evidence from the semiarid Andean subtropics

Abstract: Question: What is the effect of shrubs on herbaceous species richness at three spatial scales: quadrat, site, and region? Location: Prepuna, subtropical semi‐arid Andes. Methods: At eight sites, we recorded the presence of herbaceous species in spaces beneath shrubs/small trees and in open areas. At the quadrat scale, the average species number per quadrat was calculated and compared between the two microhabitats (shrubs/open). At the local (site) scale, all quadrats of each site were pooled according to mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Positive associations between shrubs and herbaceous species are frequently reported from environments that experience high abiotic stress, because shrubs can modify local abiotic conditions, making environmental conditions more favorable for growth (Callaway et al, 1996;Lopez et al, 2009;Maestre et al, 2009). Less is known about the influence of a shrub layer on understory vegetation in temperate forests, where abiotic stress is benign.…”
Section: Discussionmentioning
confidence: 97%
“…Positive associations between shrubs and herbaceous species are frequently reported from environments that experience high abiotic stress, because shrubs can modify local abiotic conditions, making environmental conditions more favorable for growth (Callaway et al, 1996;Lopez et al, 2009;Maestre et al, 2009). Less is known about the influence of a shrub layer on understory vegetation in temperate forests, where abiotic stress is benign.…”
Section: Discussionmentioning
confidence: 97%
“…Unexpectedly, unmanipulated native plant abundance increased in response to the transplanted species in the restoration quadrats but not in any control quadrats where no transplants were installed. This observation suggested that positive plant interactions could be taking place, providing the unique opportunity to explore the resulting environmental factors responsible for positive community-level changes in vegetation among dune habitats that are characterized by different types of abiotic stress (Brooker et al, 2008;Lopez, Larrea-Alcazar, and Ortuno, 2009). Our goals were (1) to investigate if transplants significantly increased vegetation cover or species richness, possibly indicating positive species interactions (Bertness and Shumway, 1993;Callaway, 1995;Stachowicz, 2001); (2) to determine whether disturbance effects from transplanting played a role; and (3) to test two environmental factors involved in positive interactions (e.g., shading and fluctuations in soil moisture) to explain changes in vegetation across the three habitat zones.…”
Section: Introductionmentioning
confidence: 97%
“…In these environments, for example, many stresses occur, including salt spray, substrate movement, high temperatures, and low nutrient and water availability; they change along a gradient of unique habitats (Brooker et al, 2008;Hesp, 1991;Lopez, Larrea-Alcazar, and Ortuno, 2009;Noy-Meir, 1973). Barrier islands can be partitioned into three habitat zones: foredune, interdune, and backdune habitats (Ehrenfeld, 1990;Lewis, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, shrubs are drought-tolerant plants having usually xerophytic traits and well-developed chemical and structural defenses against water shortage and herbivores (Bertiller et al, 1991;Ivanov et al, 2008;Campanella and Bertiller, 2009). Due to these characteristics, shrubs may facilitate the establishment and growth of perennial grasses by creating ameliorated microenvironments around them or protecting herbaceous plants from herbivores Sala, 1994, 1999;Bertiller et al, 2002;Bertiller and Ares, 2008;Lopez et al, 2009).…”
Section: Introductionmentioning
confidence: 99%